ANALISIS PENGENDALIAN MUTU PRODUK ROTI MANIS DENGAN METODE STATISTICAL PROCESS CONTROL (SPC) PADA KAMPAR BAKERY BANGKINANG - Norawati, Suarni; Zulher, Zulher (Jurnal Menara Ekonomi : Pelatihan dan Kajian Ilmiah Bidang Ekonomi, 2019)
The purpose of this study was to determine the quality control process, and to find out the results of the application of the SPC method in the sweet bread. Quality control the method used in this study was the method of statistical process control (SPC), which is one statistical quality control tool that is used to determine the control of the process carried out.Based on the results of the study, it can be seen that the stages of the quality control process of the sweet bread products in Kampar Bakery are carried out in three stages, namely the quality control of raw materials, production process, and the final products (finishing). Based on calculation using the control chart diagram in the SPC method, Kampar Bakery is still under control and relatively stable, even though there is still product damage. Resulting from the results of the histogram diagram, it is known that the most dominant type of the product damage is due to incompatible size. Based on the casual diagram the main factors that the cause damage are labor, machine, raw materials, and environmental factors.Keywords : Quallity Control, SPC Method